1994
DOI: 10.1016/0014-5793(94)00836-1
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning of the human type VIII adenylyl cyclase

Abstract: A cDNA coding for a human type VIII adenylyl cyclase has been isolated from human newborn brain-stem tissue. This cDNA is 6,005 bp long and encodes for a protein of 1251 amino acids, exhibiting the two sets of six transmembrane spanning regions and the hydrophobicity profile typical of other mammalian adenylyl cyclases. Comparison with the rat form shows that they share 97% identity in amino acids. Type VIII adenylyl cyclase is unique in that it has both a long carboxy terminal and a long amino terminal tail. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 32 publications
1
24
0
Order By: Relevance
“…ADCY8 is clearly expressed to a comparable extent in pancreatic β-cells in rodents and in humans although levels are low as reported previously [6]. Expression of ADCY8 in human islets has also been reported most recently using a primer different from ours [29] and the long-known existence of splice variants [36] may explain its reported absence in certain studies.…”
Section: Discussionmentioning
confidence: 70%
“…ADCY8 is clearly expressed to a comparable extent in pancreatic β-cells in rodents and in humans although levels are low as reported previously [6]. Expression of ADCY8 in human islets has also been reported most recently using a primer different from ours [29] and the long-known existence of splice variants [36] may explain its reported absence in certain studies.…”
Section: Discussionmentioning
confidence: 70%
“…Oligonucleotide primers specifically designed to be complementary to the cDNA sequence of human ACs, rather than rat, murine or bovine sequences, have been employed to demonstrate the presence of mRNA encoding for a variety of AC isoforms. At present, human sequence data exist for only five AC isoforms, namely AC I (Villacres et al 1993), AC II (Stengel et al 1992), AC III (Yang et al 1999), AC VIII (Defer et al 1994) and AC IX (Hacker et al 1998). By utilising primers based on these published human sequences we have demonstrated the presence of mRNA encoding for Groups 1 (types I, III and VIII), 2 (AC II) and 4 (AC IX) in both pregnant and non-pregnant human myometrium.…”
Section: Discussionmentioning
confidence: 85%
“…15 Mice were screened for the presence of the transgene by Southern blot performed on tail genomic DNA. Two founders were identified and propagated by crossbreeding with C57BL/6 wild-type mice.…”
Section: Generation Of Transgenic Micementioning
confidence: 99%
“…12 In contrast, AC1 and AC8, which are essentially expressed in the central nervous system, are activated by Ca 2ϩ through the Ca 2ϩ /calmodulin complex. [13][14][15] In this study, we describe transgenic mice overexpressing the Ca 2ϩ /calmodulin-activatable isoform AC8 specifically targeted to cardiomyocytes. Surprisingly, we observed that AC8 overexpression has no effect on the viability of the animals but leads to a higher basal intrinsic contractility that is unresponsive to further ␤-AR stimulation.…”
mentioning
confidence: 99%